Learning from Prices: Public Communication and Welfare - Amador, Manuel; Weill, Pierre-Olivier (Journal of Political Economy, 2010)
We study the effect of releasing public information about productivity or monetary shocks using a micro-founded macroeconomic model in which agents learn from the distribution of nominal prices. While a public release has the direct beneficial effect of providing new information, it also has the indirect adverse effect of reducing the informational efficiency of the price system. We show that the negative indirect effect can dominate. Thus, the public information release may increase uncertainty about the monetary shock and reduce welfare. We find that the optimal communication policy is always to release either all or none of the information.